(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective:The aim is to publish the case report of the rarely occurring and life threatening ectopic pregnancy developing in a Caesarean section scar causing uterine rupture. Methods and Results: This patient was diagnosed initially as a case of incomplete abortion. Other possible diagnoses were molar pregnancy, mass in the cervix. She was admitted in hospital for evacuation and curettage. During the procedure she developed severe pervaginal bleeding leading to hypovolumic shock. So decision was taken for emergency laparotomy. After opening the abdomen rupture was found in the lower uterine segment extending upto upper part of cervix. So hysterectomy was performed and histopathology confirmed the diagnosis of ectopic pregnancy that developed in a Caesarean section scar Analysis of the womens obstetric history revealed that she had been previously operated because of breech presentation. Conclusion: Heightened awareness of the possibility of pregnancy in caesarean scar and early diagnosis by means of transvaginal sonography along with colour doppler can improve outcome and minimize the need for emergency extended surgery Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 83-86